‘Nature of Mathematics weiterdenken’: First findings of an empirical study among prospective teachers and mathematics students at the University of Vienna - Woltron, Felix (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
The purpose of this paper is to present first findings, reflect on the chosen methodology and create hypotheses for the main project ‘Nature of Mathematics weiterDenken’, which is currently under development, examining and comparing mathematical world views and domain specific beliefs of prospective teachers and mathematics students. The analysis of the data collected by using an online questionnaire containing 93 closed items (five step Likert-scale) indicates that there is no statistically significant difference in mathematical world views among the surveyed subgroups (n = 75), either cross-sectionally (prospective teachers/mathematics students) or quasi-longitudinally (within each sample group at three different points of measurement).